IMPLEMENTASI KEBIJAKAN PROGRAM BANTUAN SISWA MISKIN (BSM) TINGKAT SMP DI KOTA SEMARANG ( Studi Pada SMP Negeri 27 Semarang) - Sofianty, Winda; Suryaningsih, Margaretha; Marom, Aufarul (Journal of Public Policy and Management Review, 2015)
The aid program poor students (BSM) supported by related to the low participation in education especially on the poor because of high cost of education either directly or indirectly. Then the government seek to students from the poor can continue to go to school without the obstacles in the fulfillment of the cost of schools by issuing a program that is help poor students (BSM) . This policy rests on a presidential regulation (Perpres) no. 15 years in 2010 on the acceleration of poverty reduction . The implementation of this research is to find out the factors influencing the implementation and to identify factors supporting and policy implementation, poor students level junior high schools in semarang city (Study in junior high school 27 Semarang). This objective can be achieved through the process of implementation and the factors affecting implementation according to george c .Edward iii namely communication , resources ,disposition , bureaucracy and structures. The results of this research show that the Policies Help poor students (BSM) at Junior High School 27 Semarang can already help students to be able to continue his education, although in practice there are still various obstacles such as the lack of socialization, the number of personnel is still limited as well as the supervision has not been optimal.